Dynamic behaviour and sensitivity analysis of 5kW PEMFC stack simulation - Ahmad, Arshad; Ramli, Ahmad Raoof (Universiti Malaysia Sabah, 2003)
This paper describes a three dimensional 5 kW PEMFC stack dynamic model. Both time and spatial dependence are considered. Dynamic response and sensitivity analyses of the stack are carried out using MATLAB and Simulink modules. The results highlights the three dimensional distributions of species concentrations, power density and temperature of model. The effects of feed flowrates on the stack power performance are illustrated. The results confirmed that the model developed as a reasonable representation of the fuel cell stack system.